Enhancing emotional intelligence through creative process in KOMSAS drama for secondary school students: the design and development of create-EMO / Nurul Fasheha Razali, Harrinni Md Noor and Farhana Wan Yunus - Razali, Nurul Fasheha; Md Noor, Harrinni; Wan Yunus, Farhana (Universiti Teknologi MARA, 2022)
The recent Covid-19 pandemic has seen an increased number of cases of mental health issues. Our education system has taken a considerable turn to meet teaching and learning demands from conventional to virtual methods. Students need to stay at home and go on virtual classroom mode. Though the implementation of virtual learning is not new in this 21st Century, the abrupt change in learning methods with the absence of peers and teachers has caused many students to feel frustrated and stressed out. Therefore, it is crucial and timely to focus on students' emotional well-being during this new norm and start to infuse emotional intelligence (EI) into their lessons. This research explores the design and development stages of the teaching and learning module called Create-EMO. Research data was only based on literature reviews and interviews among experts. A Create-EMO module was designed and developed by incorporating EI through creative processes (CP) for the Secondary 4 Drama Malay literature component, KOMSAS (Komponen Sastera). Create-EMO was also designed and developed based on the ASSURE model and Goleman's four main EI domains - self-awareness, self-management, social awareness and social skills. This module also includes Wallas' four-stage creative process - preparation, incubation, illumination and verification. The module also allows students to work collaboratively on a shared project as they can view problems and issues from varying perspectives, thus raising their awareness of the issues involved.